Desarrollo del Sistema de Mensajería de Texto para Telefonía Fija - Alfaro-Hernández, Eduardo; Mendivil-Piedra, Victor (Instituto Tecnológico de Costa Rica, 2006)
The technological innovation and search of new services is an ideal of the Instituto Costarricense de Electricidad (ICE), which makes the necessity to offer and to enlarge the communication services among its clients. The phone communication is divided in the cellular telephony and fixed telephony. At the moment, the main income of ICE it is given by means of the fixed telephony services. The cellular telephony is taking preference among the clients, therefore it’s necessary to offer new services for fixed telephony. The objective of the project is to develop a new service for the clients of the fixed telephony network, which consists in providing the short text message service (SMS) for fixed lines. In order to standardize the service, in the development of the system, protocols and norms defined by the European Telecommunications Standards Institute (ETSI) have been taken as a reference. The importance of using an international standard resides in the possibility of using commercial terminals (telephones) designed for the SMS. This way, the project is focused in developing the center of messages (SM-SC) and to create the application that manages the protocol. The center of messages was developed in an APEX platform of added value, under a Windows 2000 environment. This platform is connected to the Public Switched Telephone Network (PSTN) through a channel E1 with signaling ISDN. In the future, one of ICE’s goal is to allow the integration of the different services in all technologies (mobile and fixed telephony). With this project the SMS is allowed between fixed telephones, the use of the standard leaves a door open to be able to develop the exchange of text messages with the cellular telephony.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2006.
Keywords: Mensajes; Códigos; Diagramas; Datos; Información; Voz